Analisis Kesalahan Berbahasa dalam Podcast Raymond Chin Sebagai Bentuk Fenomena Bahasa - Rd Bily Parancika; Mohammad Aris; Sifa Fauziah (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Language has a vital role as a means of communication and social identity. In the digital era, new media such as podcasts can influence changes in the language used by society. This study aims to analyze the form of language errors in the podcasts studied, namely Raymond Chin's podcast with Bintang Emon, Ustaz Felix Siauw, and Koiyo Cabe. The research method used is qualitative descriptive with data collection techniques through transcription and recording. The results of the study show that many of the language errors made are phonological errors or language sounds and also morphology or word form errors due to regional language interference and communication styles in casual conversation. This phenomenon reflects the change in language norms in the digital era, where the use of language has become more flexible, adaptive and informal.